The Status of antimicrobial resistance in Campylobacter spp. isolated from animals and humans in Southeast Asia: a review - Jafari, Saeid; Ebrahimi, Mahdi; Luangtongkum, Taradon (The Thai Journal of Veterinary Medicine, 2020)
Campylobacter is considered to be a major foodborne pathogen associated with human bacterial gastroenteritis in many parts of the world. Southeast Asia (SEA) has been challenging for infectious diseases and antimicrobial resistance in recent years. Antibiotic resistance in Campylobacter isolates has been reported in humans and animals in this region. Since the SEA region is one of the top tourist destinations of the world, the provision of safe food is of importance for the travel-related foodborne infections. Therefore, it is essential to elucidate the status of antibiotic resistance of Campylobacter spp. in the SEA region to reduce the impact of infection and to implement mitigation strategies. This review provides further insights into the true burden of the trend of antimicrobial resistance in Campylobacter spp. in the SEA region. Based on the published data, antimicrobial resistance of both human and animal in Campylobacter isolates is becoming increasingly common in SEA, especially to fluoroquinolones and tetracycline. Therefore, appropriate interventions are required to minimize Campylobacter contamination and to harmonize the monitoring of antimicrobial resistance in SEA.